Comparative study of Mentha species growing wild in Egypt: LC-ESI-MS analysis and chemosystematic significance - Mona M. Marzouk, Sameh R. Hussein, Ahmed Elkhateeb, Mona El-shabrawy, El-Sayed S. Abdel-Hameed & , Salwa A. Kawashty (Journal of Applied Pharmaceutical Science, 2018)
Mentha longifolia (L.) Huds. and Mentha pulegium L. are growing wild in Egyptian flora, they have many biological activities and commonly used as traditional herbal medicines. The aqueous methanolic extracts of the two Egyptian species were subjected to a comparative study for the first time using the LC-ESI-MS fingerprint. 43 compounds belonging to different chemical classes (flavone, flavonol, flavanone, C-glycosylflavone, phenolic acids and their glycosides) have been identified. The identified compounds can be used as chemosystematic markers and further our knowledge of the infraspecific relationship between the studied species. Further isolation and in vitro testing of metabolites will provide more evidence for the possible uses of Mentha sp.
Keywords: Mentha longifolia, Mentha pulegium, LC-ESI-MS, Flavonoids, Chemosystematics.